Macrophage DCLK1 promotes atherosclerosis via binding to IKKβ and inducing inflammatory responses - Zhuqi Huang; Sirui Shen; Xue Han; Weixin Li; Wu Luo; Liming Lin; Mingjiang Xu; Yi Wang; Weijian Huang; Gaojun Wu; Guang Liang (EMBO Molecular Medicine, 2023)
Abstract Atherosclerosis is a chronic inflammatory disease with high morbidity and mortality rates worldwide. Doublecortin‐like kinase 1 (DCLK1), a microtubule‐associated protein kinase, is involved in neurogenesis and human cancers. However, the role of DCLK1 in atherosclerosis remains undefined. In this study, we identified upregulated DCLK1 in macrophages in atherosclerotic lesions of ApoE−/− mice fed an HFD and determined that macrophage‐specific DCLK1 deletion attenuates atherosclerosis by reducing inflammation in mice. Mechanistically, RNA sequencing analysis indicated that DCLK1 mediates oxLDL‐induced inflammation via NF‐κB signaling pathway in primary macrophages. Coimmunoprecipitation followed by LC–MS/MS analysis identified IKKβ as a binding protein of DCLK1. We confirmed that DCLK1 directly interacts with IKKβ and phosphorylates IKKβ at S177/181, thereby facilitating subsequent NF‐κB activation and inflammatory gene expression in macrophages. Finally, a pharmacological inhibitor of DCLK1 prevents atherosclerotic progression and inflammation both in vitro and in vivo. Our findings demonstrated that macrophage DCLK1 promotes inflammatory atherosclerosis by binding to IKKβ and activating IKKβ/NF‐κB. This study reports DCLK1 as a new IKKβ regulator in inflammation and a potential therapeutic target for inflammatory atherosclerosis.